L’acquisition de la compétence sémantique chez les apprenants chinois du FLE : analyse au travers des valeurs sociales complexes des mots « travail » et « loisirs » - Xiaoxiao Xia (Recherches en Éducation)
This paper focuses on the comparison of the linguistic construction of complex social values and lexical meanings’ reconstruction in the discourse between Chinese and French native speakers and Chinese learners of French. By analyzing the perceptions of the meanings of the words "work" and "leisure", we try to find out the linguistic stereotypes of the two languages and the influence on the acquisition of semantic competence in foreign language learners. The data was collected through a questionnaire with a total of 40 university-student informants. The results show that although the French and the Chinese share roughly the same core of these two words, stereotypes are different because of cultural differences. Moreover, even if the public are of the same nationality, learning a foreign language and living in the country of the target language lead to differences in the acquisition of lexical meanings.